PENINGKATAN KINERJA GURU MELALUI KARAKTERISTIK INDIVIDU DAN KOMPETENSI GURU - Ernest Grace; Erbin Chandra; Marthin Hutler Ambarita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The performance of teachers who are still not in accordance with their abilitiestoday is a problem in the management of education. There are several factorsthat can affect the performance of the teacher, including individualcharacteristics and teacher competence, but these two factors also still haveshortcomings in their management. For this reason, the purpose of this study isto examine the influence of individual characteristics and teacher competencieson teacher performance at the teachers of SMK Negeri 1 Siantar, SimalungunRegency, totaling 24 people. This study uses quantitative and qualitative analysis with the use of validity and reliability tests where the results are valid andreliable. For the normality test that the data has a normal distribution, then forthe simple regression equation and multiple regression that the results of thecorrelation coefficient of individual characteristics and teacher competence onteacher performance are positive. For the partial test that individualcharacteristics have a positive and significant effect on teacher performance, forthe partial test of the teacher competency variable on teacher performance it haspositive and significant results. The results for the simultaneous test are knowntogether that individual characteristics and teacher competencies have a positiveand significant effect on teacher performance, this shows that when individualcharacteristics and teacher competencies are good, teacher performance willalso be good.